Manhattan : Letters from Prehistory - Cixous, Helene, 1937- (Book collections on Project MUSE., 2023)
"Manhattan is the tale of a young French scholar who travels to the United States in 1965 on a Fulbright Fellowship to consult the manuscripts of beloved authors. In Yale University's Beinecke Library, tantalized by the conversational and epistolary brilliance of a fellow researcher, she is lured into a picaresque and tragic adventure. Meanwhile, back in France, her children and no-nonsense mother await her return. A young European intellectual's first contact with America and the city of New York are the background of this story. The experience of Manhattan haunts this labyrinth of a book as, over a period of thirty-five years, its narrator visits and revisits Central Park and a half-buried squirrel, the Statue of Liberty and a never again to be found hotel in the vicinity of Morningside Heights: a journey into memory in which everything is never the same. Traveling from library to library, France to the United States, Shakespeare to Kafka to Joyce, Manhattan deploys with gusto all the techniques for which Cixous's fiction and essays are known: rapid juxtapositions of time and place, narrative and description, analysis and philosophical reflection. It investigates subjects Cixous has spent her life probing: reading, writing, and the "omnipotence-other" seductions of literature; a family's flight from Nazi Germany and postcolonial Algeria; childhood, motherhood, and, not least, the strange experience of falling in love with a counterfeit genius"--